Body fat, pericardial fat, liver fat and arterial health at age 10 years. Issue 10 (4th May 2022) - Monasso, Giulietta S.; Santos, Susana; Silva, Carolina C. V.; Geurtsen, Madelon L.; Oei, Edwin; Gaillard, Romy; Felix, Janine F.; Jaddoe, Vincent W. V.
Summary: Background: Body mass index is associated with carotid intima‐media thickness and distensibility in adults and children. Objective: To examine whether general and specific fat depots are associated with these markers of arterial health at school age. Methods: This cross‐sectional analysis was embedded in a population‐based prospective cohort study among 4708 children aged 10 years. Body, lean and fat mass index were estimated by dual‐energy X‐ray absorptiometry. Pericardial, visceral and liver fat were estimated by magnetic resonance imaging. Carotid intima‐media thickness and distensibility were measured by ultrasound. Results: A 1‐standard‐deviation‐score (SDS) higher body mass index was associated with higher carotid intima‐media thickness (0.06 SDS, 95% confidence interval [CI]: 0.03–0.08) and lower distensibility (−0.17 SDS, 95% CI: −0.20 to −0.14). These associations tended to be similar for lean mass index. A 1‐SDS higher fat mass index was associated with lower carotid intima‐media thickness (−0.08 SDS, 95% CI: −0.11 to −0.05) and lower distensibility (−0.10 SDS, 95% CI: −0.14 to −0.07). A 1‐SDS higher liver fat fraction was associated with lower carotid intima‐media thickness (−0.04 SDS, 95% CI: −0.08 to −0.00) and lower distensibility (−0.06 SDS, 95% CI: −0.10 to −0.03). We observed similar associations for visceral fat. Conclusions: At school age, lean and fat mass seem to be differentially related to carotid intima‐media thickness but not distensibility. Arterial development might be affected by lean mass, general and specific fat mass.